Occurrence, Characterization, and Potential Ecological Risks of Microplastics in the Himalayan Riverine Systems - Deepa Kumari; Ramendra Pati Pandey; Ankur Rajpal; H. C. Sudheeksha; Smriti Arora (Bulletin of Environmental Contamination and Toxicology, 2026)

Spectroscopic Analysis of 4-MeO-TPA with Metal Oxide Nano-Assembly: Insights on Fluorescence Quenching and FRET - V. V. Koppal; R. Venkatesh; N. R. Banapurmath; Kalpana Sharma; Deepa H. K (Journal of Fluorescence, 2025)

Spectroscopic and Computational Analysis of 5PPD-CeO2: Insights from Fluorescence Quenching and FRET Studies - Kalpana Sharma; Varsha V. Koppal; Raviraj Kusanur; Deepa H. K (Journal of Fluorescence, 2025)

Evaluation of diverse blackgram (Vigna mungo (L.) Hepper) germplasm accessions for root-knot nematode resistance and genetic diversity study - Bharat H. Gawade; Lovely Kumari; Zakaullah Khan; Ankit Saroha; Shraddha Ujjainwal; Deepa Pal; Gayacharan; Kuldeep Tripathi; Padmavati G. Gore; V. Celia Chalam; Dhammaprakash Pandhari Wankhede (Genetic Resources and Crop Evolution, 2025)

Exploring the molecular binding mechanism of 6-fluoro, 4-hydroxy, 2- methyl quinoline with TiO2 nanoparticles: A spectroscopic, thermodynamic, and insights into the solvatochromic effect - Deepa H. Krishne; Kalpana Sharma; A. Jagannatha Reddy; V. V. Koppal (Journal of Fluorescence, 2024)

Integrating Multiscale Geospatial Analysis for Monitoring Crop Growth, Nutrient Distribution, and Hydrological Dynamics in Large-Scale Agricultural Systems - Olatunde D. Akanbi; Deepa C. Bhuvanagiri; Erika I. Barcelos; Arafath Nihar; Brian Gonzalez Hernandez; Jeffrey M. Yarus; Roger H. French (Journal of Geovisualization and Spatial Analysis, 2024)
Monitoring crop growth, soil conditions, and hydrological dynamics are imperative for sustainable agriculture and reduced environmental impacts. This interdisciplinary study integrates remote sensing, digital soil mapping, and hydrological data to elucidate intricate connections between these factors in the state of Ohio, USA. Advanced spatiotemporal analysis techniques were applied to key datasets, including the MODIS sensor satellite imagery, USDA crop data, soil datasets, Aster GDEM, and USGS stream gauge measurements. Vegetation indices derived from MODIS characterized crop-specific phenology and productivity patterns. Exploratory spatial data analysis show relationships of vegetation dynamics and soil properties, uncovering links between plant vigor, edaphic fertility, and nutrient distributions. Correlation analysis quantified these relationships and their seasonal evolution. Examination of stream gauge data revealed insights into spatiotemporal relationships of nutrient pollution and stream discharge. By synthesizing diverse geospatial data through cutting-edge data analytics, this work illuminated complex interactions between crop health, soil nutrients, and water quality in Ohio. The methodology and findings provide actionable perspectives to inform sustainable agricultural management and environmental policy. This study demonstrates the significant potential of open geospatial resources when integrated using a robust spatiotemporal framework. Integrating additional measurements and high-resolution data sources through advanced analytics and interactive visualizations could strengthen these insights.

Multiple toxins and a protease contribute to the aphid‐killing ability of Pseudomonas fluorescens PpR24 - Deepa Paliwal; Mojgan Rabiey; Tim H. Mauchline; Keywan Hassani‐Pak; Ralf Nauen; Carol Wagstaff; Simon Andrews; Chris Bass; Robert W. Jackson (Environmental Microbiology, 2024)
Aphids are globally important pests causing damage to a broad range of crops. Due to insecticide resistance, there is an urgent need to develop alternative control strategies. In our previous work, we found Pseudomonas fluorescens PpR24 can orally infect and kill the insecticide‐resistant green‐peach aphid ( Myzus persicae ). However, the genetic basis of the insecticidal capability of PpR24 remains unclear. Genome sequencing of PpR24 confirmed the presence of various insecticidal toxins such as Tc (toxin complexes), Rhs (rearrangement hotspot) elements, and other insect‐killing proteases. Upon aphids infection with PpR24, RNA‐Seq analysis revealed 193 aphid genes were differentially expressed with down‐regulation of 16 detoxification genes. In addition, 1325 PpR24 genes (542 were upregulated and 783 downregulated) were subject to differential expression, including genes responsible for secondary metabolite biosynthesis, the iron‐restriction response, oxidative stress resistance, and virulence factors. Single and double deletion of candidate virulence genes encoding a secreted protease (AprX) and four toxin components (two TcA‐like; one TcB‐like; one TcC‐like insecticidal toxins) showed that all five genes contribute significantly to aphid killing, particularly AprX. This comprehensive host–pathogen transcriptomic analysis provides novel insight into the molecular basis of bacteria‐mediated aphid mortality and the potential of PpR24 as an effective biocontrol agent.

Saturated Fat Intake and the Prevention and Management of Cardiovascular Disease in Adults: An Academy of Nutrition and Dietetics Evidence-Based Nutrition Practice Guideline - Sarah A. Johnson; Carol F. Kirkpatrick; Nicole H. Miller; Jo Ann S. Carson; Deepa Handu; Lisa Moloney (Journal of the Academy of Nutrition and Dietetics, 2023)

Salient findings on diagnostics, pathogen diversity and management of wilt of chickpea caused by Fusarium oxysporum f. sp. ciceris in North Karnataka - Gururaj Sunkad; H Deepa; Kasi Rao Mediga; Meghana Patil (Indian Phytopathology, 2023)

Microstructure, rheological and water mobility behaviour of plant-based protein isolates (pea and quinoa) and locust bean gum mixtures - Deepa Agarwal; Esther H.-J. Kim; Limei Feng; Cath Wade; Gert-Jan Moggré; Marco P. Morgenstern; Duncan I. Hedderley (Food Research International, 2023)

Rapid assessment of insect pollination services to inform decision‐making - Fabrizia Ratto; Tom D. Breeze; Lorna J. Cole; Michael P. D. Garratt; David Kleijn; Bill Kunin; Denis Michez; Rory O'Connor; Jeff Ollerton; Robert J. Paxton; Guy M. Poppy; Simon G. Potts; et al. (Conservation Biology, 2022)
Pollinator declines have prompted efforts to assess how land‐use change affects insect pollinators and pollination services in agricultural landscapes. Yet many tools to measure insect pollination services require substantial landscape‐scale data and technical expertise. In expert workshops, 3 straightforward methods (desk‐based method, field survey, and empirical manipulation with exclusion experiments) for rapid insect pollination assessment at site scale were developed to provide an adaptable framework that is accessible to nonspecialist with limited resources. These methods were designed for TESSA (Toolkit for Ecosystem Service Site‐Based Assessment) and allow comparative assessment of pollination services at a site of conservation interest and in its most plausible alternative state (e.g., converted to agricultural land). We applied the methods at a nature reserve in the United Kingdom to estimate the value of insect pollination services provided by the reserve. The economic value of pollination services provided by the reserve ranged from US$6163 to US$11,546/year. The conversion of the reserve to arable land would provide no insect pollination services and a net annual benefit from insect‐pollinated crop production of approximately $1542/year (US$24∙ha –1 ∙year –1 ). The methods had wide applicability and were readily adapted to different insect‐pollinated crops: rape ( Brassica napus ) and beans ( Vicia faba ) crops. All methods were rapidly employed under a low budget. The relatively less robust methods that required fewer resources yielded higher estimates of annual insect pollination benefit.

Patient-Reported Outcome Severity and Emotional Salience Network Disruption in Multiple Sclerosis - Tom A. Fuchs; Caila B. Vaughn; Ralph H. B. Benedict; Bianca Weinstock-Guttman; Niels Bergsland; Dejan Jakimovski; Deepa Ramasamy; Robert Zivadinov; Michael G. Dwyer (Brain Imaging and Behavior, 2022)

Improvement in growth and yield of strawberry (Fragaria × ananassa Duch.) by mulch colour - Namrta Singh; Deepa H. Dwivedi; Sachin Kishor; Sutanu Maji (Environmental Sustainability, 2021)

Necroptosis increases with age in the brain and contributes to age-related neuroinflammation - Nidheesh Thadathil; Evan H. Nicklas; Sabira Mohammed; Tommy L. Lewis; Arlan Richardson; Sathyaseelan S. Deepa (GeroScience, 2021)
Chronic inflammation of the central nervous system (CNS), termed neuroinflammation, is a hallmark of aging and a proposed mediator of cognitive decline associated with aging. Neuroinflammation is characterized by the persistent activation of microglia, the innate immune cells of the CNS, with damage-associated molecular patterns (DAMPs) being one of the well-known activators of microglia. Because necroptosis is a cell death pathway that induces inflammation through the release of DAMPs, we hypothesized that an age-associated increase in necroptosis contributes to increased neuroinflammation with age. The marker of necroptosis, phosphorylated form of MLKL (P-MLKL), and kinases in the necroptosis pathway (RIPK1, RIPK3, and MLKL) showed a region-specific increase in the brain with age, specifically in the cortex layer V and the CA3 region of the hippocampus of mice. Similarly, MLKL-oligomers, which cause membrane binding and permeabilization, were significantly increased in the cortex and hippocampus of old mice relative to young mice. Nearly 70 to 80% of P-MLKL immunoreactivity was localized to neurons and less than 10% was localized to microglia, whereas no P-MLKL was detected in astrocytes. P-MLKL expression in neurons was detected in the soma, not in the processes. Blocking necroptosis using Mlkl −/− mice reduced markers of neuroinflammation (Iba-1 and GFAP) in the brains of old mice, and short-term treatment with the necroptosis inhibitor, necrostatin-1s, reduced expression of proinflammatory cytokines, IL-6 and IL-1β, in the hippocampus of old mice. Thus, our data demonstrate for the first time that brain necroptosis increases with age and contributes to age-related neuroinflammation in mice.

Optimization and scale-up of laccase production by Bacillus sp. BAB-4151 isolated from the waste of the soap industry - T. Deepa; A. K. Gangwane; R. Z. Sayyed; H. P. Jadhav; Mehjabeen (Environmental Sustainability, 2020)

Zinc and phosphate solubilizing Rhizobium radiobacter (LB2) for enhancing quality and yield of loose leaf lettuce in saline soil - Maya Verma; Anoop Singh; Deepa H. Dwivedi; Naveen Kumar Arora (Environmental Sustainability, 2020)

Chickpea wilt: status, diagnostics and management - Gururaj Sunkad; H. Deepa; T. H. Shruthi; Dinesh Singh (Indian Phytopathology, 2019)

The potential role of necroptosis in inflammaging and aging - Gordon H. Royce; Holly M. Brown-Borg; Sathyaseelan S. Deepa (GeroScience, 2019)

Accelerated decline in cognition in a mouse model of increased oxidative stress - Sreemathi Logan; Gordon H. Royce; Daniel Owen; Julie Farley; Michelle Ranjo-Bishop; William E. Sonntag; Sathyaseelan S. Deepa (GeroScience, 2019)

Genetic mapping of the European canker (Neonectria ditissima) resistance locus Rnd1 from Malus ‘Robusta 5’ - Vincent G. M. Bus; Reiny W. A. Scheper; Monika Walter; Rebecca E. Campbell; Biff Kitson; Lauren Turner; Brent M. Fisher; Sarah L. Johnston; Chen Wu; Cecilia H. Deng; Gagandeep Singla; Deepa Bowatte; et al. (Tree Genetics & Genomes, 2019)

Synthesis of magnetic carbon nanocomposites by hydrothermal carbonization and pyrolysis - M. T. H. Siddiqui; Sabzoi Nizamuddin; Humair Ahmed Baloch; N. M. Mubarak; Deepa K. Dumbre; Inamuddin; Abdullah M. Asiri; A. W. Bhutto; Madapusi Srinivasan; G. J. Griffin (Environmental Chemistry Letters, 2018)

Combined effects of agrochemicals and ecosystem services on crop yield across Europe - Vesna Gagic; David Kleijn; András Báldi; Gergely Boros; Helene Bracht Jørgensen; Zoltán Elek; Michael P. D. Garratt; G. Arjen de Groot; Katarina Hedlund; Anikó Kovács‐Hostyánszki; Lorenzo Marini; Emily Martin; et al. (Ecology Letters, 2017)
Simultaneously enhancing ecosystem services provided by biodiversity below and above ground is recommended to reduce dependence on chemical pesticides and mineral fertilisers in agriculture. However, consequences for crop yield have been poorly evaluated. Above ground, increased landscape complexity is assumed to enhance biological pest control, whereas below ground, soil organic carbon is a proxy for several yield‐supporting services. In a field experiment replicated in 114 fields across Europe, we found that fertilisation had the strongest positive effect on yield, but hindered simultaneous harnessing of below‐ and above‐ground ecosystem services. We furthermore show that enhancing natural enemies and pest control through increasing landscape complexity can prove disappointing in fields with low soil services or in intensively cropped regions. Thus, understanding ecological interdependences between land use, ecosystem services and yield is necessary to promote more environmentally friendly farming by identifying situations where ecosystem services are maximised and agrochemical inputs can be reduced.

The Effect of Hematocrit and Leukocyte Adherence on Flow Direction in the Microcirculation - Michael R. King; Deepa Bansal; Michael B. Kim; Ingrid H. Sarelius (Annals of Biomedical Engineering, 2004)

Is Bigger Better? Size and Pheromone Production in the Mountain Pine Beetle, Dendroctonus ponderosae Hopkins (Coleoptera: Scolytidae) - Deepa S. Pureswaran; John H. Borden (Journal of Insect Behavior, 2003)

Trace Metal Concentration in Scalp Hair of Occupationally Exposed Autodrivers - H. Vishwanathan; A. Hema; Deepa Edwin; M. V. Usha Rani (Environmental Monitoring and Assessment, 2002)